Who gets ostracized? A personality perspective on risk and protective factors of ostracism - Selma Carolin Rudert; Matthias Keller; Andrew Hales; Mirella Walker; Rainer Greifeneder (Journal of Personality and Social Psychology, 2020)
Ostracism, excluding and ignoring others, results from a variety of factors. Here, we investigate the effect of personality on the likelihood of becoming a target of ostracism. Theorizing that individuals low in conscientiousness or agreeableness are at risk of getting ostracized, we tested our hypotheses within five pre-registered studies: Four experiments investigating participants’ willingness to ostracize targets characterized by different personality traits and a reverse correlation face modelling study where we determined and subsequently validated the stereotypical face of an ostracized person. A survey study within a representative German data panel further corroborated our findings. In line with our hypotheses, persons low in conscientiousness or agreeableness provoke more ostracism intentions (Studies 1, 2, and 4), are more likely to be actually ostracized by others (Study 3), represent the stereotype of an “ostracizable” person (Study 5), and report experiencing more ostracism (Study 6). Effects remained stable even after controlling for likeability of the target (Study 2 and 4). Moreover, being described as negative on one personality dimension could not be compensated by being described as positive on the other (Study 4). In exploratory analyses, we further investigated the effects of openness to experience, neuroticism and extraversion. In sum, we find evidence that personality affects the likelihood of becoming a target of ostracism, and that especially low agreeableness and conscientiousness represent risk factors.

Whom to punish? How observers sanction norm-violating behavior in ostracism situations. - Selma Carolin Rudert; Simone Ruf; Rainer Greifeneder (European Journal of Social Psychology, 2020)
When observing ostracism, individuals can either side with the target or the sources of ostracism. Here we demonstrate that side‐taking depends on whether the target previously acted in adherence to or in violation of perceived social norms. In four studies, a target behaved either norm‐consistently or violated a social norm, and was subsequently either excluded by the sources or was not. Next, participants could sanction the behavior of the observed persons by refraining to assign money (Studies 1 and 2), or by subtracting money from a bonus (Studies 3 and 4). Observers assigned less money to the sources when these excluded a norm‐consistent target. However, when the target had violated a social norm before, participants assigned less money to the target instead. These results have far‐reaching implications because the (in)actions of neutral individuals can legitimize the sources’ behavior, or help a target under attack.

About flames and boogeymen: Social norms affect individuals’ construal of social exclusion - Rainer Greifeneder; Selma Carolin Rudert (Current Directions in Ostracism, Social Exclusion and Rejection Research, 2019)
The first reaction to social exclusion is often described as a reflexive pain reaction that threatens individual’s fundamental needs. This reflexive reaction has usually been conceptualized as direct and independent of situational influence. In this chapter, we highlight a different perspective that conceptualizes reactions to ostracism as fundamentally cognitively mediated. This perspective emphasizes the role of individuals’ subjective construal of the objective not-being-part situation. While many frames of interpretation may exist to guide subjective construal, we put the spotlight on social norms as one particularly important frame of interpretation in daily life. We argue that if exclusion is interpreted as a violation of a prevailing inclusion norm, individuals will experience pain and threat. In contrast, if exclusion is perceived as consistent with the salient norm, and if this norm is personally endorsed, the situation may not be interpreted as threatening in the first place. Evidence in support is reported and related to the larger framework of research on ostracism and social exclusion.

Current Directions in Ostracism, Social Exclusion and Rejection Research - Selma Carolin Rudert; Rainer Greifeneder; Kipling Williams (Routledge, 2019)
This edited volume provides an up-to-date review of current research on ostracism, social exclusion, and rejection. The book shows why exclusion and rejection occur, how they affect the excluded individuals, and the consequences they might have for individuals and organizations. Ostracism, social exclusion, and rejection are common phenomena, both at the individual level, such as ostracism in the classroom or at the workplace, as well as on a societal or even global scale, such as immigration or asylum policies. Examining key concepts such as the long-term effects of ostracism, the developmental and cultural perspective on ostracism, and the detrimental impact that social exclusion may have on individuals and societies, the authors provide an up-to-date overview of the research field and present new conceptual models and methodological approaches. Featuring discussion of promising areas, novel pathways for research, and cutting-edge developments, this is the most comprehensive bringing-together of research on this topic. The book gives both a broad state-of-the-art overview of the field as well as discussing cutting-edge ideas and promising areas for future research; it is essential for students, researchers of social psychology, and policy makers interested in this field.

Observing ostracism: How observers interpret and respond to ostracism situations - Selma Carolin Rudert; Rainer Greifeneder (Current Directions in Ostracism, Social Exclusion and Rejection Research, 2019)
This chapter presents an overview about how uninvolved observers perceive, interpret and evaluate ostracism and eventually, how they react to ostracism situations. Whereas research has often focused on how observers empathize with targets of ostracism and “feel their pain,” different attributions about the underlying motives for ostracism result in strong differences with regard to observers’ evaluations and behavior. If observers attribute ostracism to a malicious motive of the sources, they blame and punish the sources for it. However, if ostracism is attributed to a punitive motive following some norm-violation of the target, observers blame and punish the target. Another motive for ostracism that is perceived as socially acceptable is role-consisted ostracism. Because observers often lack information about the ostracism situation, they might revert to heuristics and stereotypes. This creates the potential for misattributions, which might then result in unfair blaming and unjust punishments of either targets or sources. In addition, observers’ intention to act on ostracism might be influenced by the motive to protect oneself from becoming a target as well. We end this chapter with several suggestions for research on observers of ostracism as well as practical interventions that can increase observers’ awareness of ostracism and assist them in making informed moral judgments.

You should go for diversity, but I’d rather stay with similar others: Psychological distance modulates one’s preference for diversity - Mariela Elena E. Jaffé; Selma Carolin Rudert; Rainer Greifeneder (Journal of Experimental Social Psychology, 2019)
Organizations often state that they value diversity. The workforce, however, is often quite homogeneous, reflecting a striking mismatch between aspirations and reality. Based on the distinction between desirability and feasibility concerns, we provide a psychological argument for this mismatch. We hypothesize that social distance influences individuals' choices regarding diversity. When being socially more distant, individuals prefer to assemble a diverse team, due to a stronger impact of pro-diversity desirability concerns. In contrast, when being socially close, individuals prefer similar team members, due to a stronger weighing of anti-diversity feasibility concerns. Four studies investigate the different decision outcomes when being socially distant compared to close. Study 1 shows that working in a diverse group is perceived as desirable, but less feasible. Study 2 investigates the impact of psychological distance on individuals' choices of working with a more different (when being socially distant) or similar partner (when being socially close). Study 3 shows that participants created a more diverse team for another person (distance condition) than for themselves (proximity condition). In Study 4, participants did not create a more diverse group for a stranger (distance condition) than for a friend (adjusted proximity condition), however, participants weighted feasibility concerns less strongly for strangers than for friends. Implications for diversity research and practice are discussed.

Bedrohung der Zugehörigkeit: Soziale Ausgrenzung in Organisationen - Selma Carolin Rudert; Rainer Greifeneder (Identität in der modernen Arbeitswelt - Neue Konzepte für Zusammenarbeit und Führung, 2018)

Dark Pathways to Achievement in Science - Stefan Janke; Martin Daumiller; Selma Carolin Rudert (Social Psychological and Personality Science, 2018)
Questionable research practices (QRPs) are a strongly debated topic in the scientific community. Hypotheses about the relationship between individual differences and QRPs are plentiful but have rarely been empirically tested. Here, we investigate whether researchers’ personal motivation (expressed by achievement goals) is associated with self-reported engagement in QRPs within a sample of 217 psychology researchers. Appearance approach goals (striving for skill demonstration) positively predicted engagement in QRPs, while learning approach goals (striving for skill development) were a negative predictor. These effects remained stable when also considering Machiavellianism, narcissism, and psychopathy in a latent multiple regression model. Additional moderation analyses revealed that the more researchers favored publishing over scientific rigor, the stronger the association between appearance approach goals and engagement in QRPs. The findings deliver first insights into the nature of the relationship between personal motivation and scientific malpractice.

Who’s to blame? Dissimilarity as a cue in moral judgments of observed ostracism episodes. - Selma Carolin Rudert; Daniela Sutter; Veronique Charlotte Corrodi; Rainer Greifeneder (Journal of Personality and Social Psychology, 2018)
When observing an ostracism episode, observers may wish to know whether ostracism is justified or not. If ostracism appears unjustified, observers will likely blame the sources and sympathize with the target; if it appears justified, observers will likely blame and devalue the target. Here we introduce the “social dissimilarity rule,” which holds that observers base their moral judgments on dissimilarities between the members of the observed group. In five studies, participants either recalled observed ostracism episodes or observed group interactions in which one group member was ostracized (e.g., in a chat or a group-working task). Results show that if similar persons exclude a dissimilar target (target is an “odd-one-out”), observers attribute ostracism to malicious motives of the ostracizers, such as ingroup favoritism, and devalue the ostracizers. However, if ostracism cannot be explained by social dissimilarity between the sources and the target, observers assume that the target is being punished for a norm deviation (punitive motive) and devalue the target. Use of the social dissimilarity rule was neither moderated by cognitive load (Study 3) nor by the perceived essentiality of the group distinction (Study 4). But if participants knew that the target previously deviated from a norm, knowledge about the situation had a stronger effect on moral judgments (Study 5) than social dissimilarity. These findings further our understanding of how observers make moral judgments about ostracism, which is important given that an observer’s moral judgment can strongly impact bystander behavior and thus target recovery and well-being.

Faced with exclusion: Perceived facial warmth and competence influence moral judgments of social exclusion - Selma Carolin Rudert; Leonie Reutner; Rainer Greifeneder; Mirella Walker (Journal of Experimental Social Psychology, 2017)
The current research investigates how facial appearance can act as a cue that guides observers' feelings and moral judgments about social exclusion episodes. In three studies, we manipulated facial portraits of allegedly ostracized persons to appear more or less warm and competent. Participants perceived it as least morally acceptable to exclude a person that appeared warm-and-incompetent. Moreover, participants perceived it as most acceptable to exclude a cold-and-incompetent looking person. In Study 2, we also varied the faces of the excluding group (i.e., the ostracizers). Results indicate that typical ostracizers are imagined as cold-and-incompetent looking. Study 3 suggests that the effect of a target's facial appearance on moral judgment is mediated by feelings of disgust. In sum, people's moral judgment about social exclusion can be influenced by facial appearance, which has many implications in intergroup research, such as for bystander intervention.

Knowing One’s Place: Parental Educational Background Influences Social Identification with Academia, Test Anxiety, and Satisfaction with Studying at University - Stefan Janke; Selma C. Rudert; Tamara Marksteiner; Oliver Dickhäuser (Frontiers in Psychology, 2017)
First-generation students (i.e., students whose parents did not attend university) often experience difficulties fitting in with the social environment at universities. This experience of personal misfit is supposedly associated with an impaired social identification with their aspired in-group of academics compared to continuing-generation students (i.e., students with at least one parent with an academic degree. In this article, we investigate how the postulated differences in social identification with the group of academics affect first-generation students’ satisfaction with studying and test anxiety over time. We assume that first-generation students’ impaired social identification with the group of academics leads to decreased satisfaction with studying and aggravated test anxiety over the course of the first academic year. In a longitudinal study covering students’ first year at a German university, we found that continuing-generation students consistently identified more strongly with their new in-group of academics than first-generation students. The influence of social identification on test anxiety and satisfaction with studying differed between groups. For continuing-generation students, social identification with the group of academics buffered test anxiety and helped them maintain satisfaction with studying over time. We could not find these direct effects within the group of first-generation students. Instead, first-generation students were more sensitive to effects of test anxiety on satisfaction with studying and vice versa over time. The results suggest that first-generation students might be more sensitive to the anticipation of academic failure. Furthermore, continuing-generation students’ social identification with the group of academics might have buffered them against the impact of negative experiences during the entry phase at university. Taken together, our findings underscore that deficit-driven approaches focusing solely on first-generation status may not be sufficient to fully understand the importance of parental educational background for students’ well-being. More specifically, continuing-generation students might reap benefits from their parental educational background. These benefits widen the social gap in academia in addition to the disadvantages of students with first-generation status. In sum, understanding the benefits of continuing-generation status has important implications for interventions aiming to reduce social class gaps in academia.

Under threat by popular vote: German-speaking immigrants’ affect and cognitions following the Swiss vote against mass immigration - Selma Carolin Rudert; Stefan Janke; Rainer Greifeneder (PLOS ONE, 2017)
A popular initiative in support of regulating future immigration to Switzerland was accepted by the electorate in 2014. Assuming that the initiative acted as an exclusionary threat for current immigrants of Switzerland, we conducted an online survey among a sample of highly-skilled German-speaking immigrants (“expats”). Participants reported having experienced negative affect following the vote. Moreover, having a more left-wing orientation, living in a political constituency that had voted pro-regulation and having proportionally few Swiss friends positively predicted negative affect following the vote. Negative affect was associated with a reported negative change in one’s attitudes towards Switzerland, increased considerations to leave the country, and impaired satisfaction with life. In sum, the results suggest that a powerful exclusionary threat such as a national vote may be experienced as distressful by highly-skilled immigrants currently living in the country.

When “We” or “They” exclude others: attributing and evaluating ostracism observed in in-groups and out-groups - Sarah Noel Arpin; Laura Froehlich; Anthony Lantian; Selma Carolin Rudert; Marleen Stelter (Comprehensive Results in Social Psychology, 2017)
Ostracism is a common social occurrence with severe psychological and behavioral consequences. Whereas many studies have focused on the perspective of ostracized individuals, our research explores observers’ perceptions of another’s ostracism, when the reason for ostracism is unclear. We investigated whether group membership affects observers’ causal attributions and evaluations of observed ostracism. Based on previous research and theory (Black Sheep Effect Ultimate Attribution Error), we hypothesized that when ostracism is observed in an out-group, the sources (i.e. the ostracizing group members) will be evaluated more negatively than the target (i.e. the ostracized individual), as the exclusion will be perceived as a violation of social norms. However, when ostracism is observed in the in-group, we hypothesized that observers would evaluate targets more negatively than the sources of ostracism. We further assumed that an intergroup bias in evaluation would be mediated by in-group-serving causal attributions. Results of an online experiment (N = 398) revealed that group membership influenced neither the attribution of responsibility nor the general evaluation of the ostracism sources and targets. Regardless of group membership, participants attributed responsibility for ostracism more to the sources than to the targets and rated targets as more likable. Though questions regarding the influence of group membership on observed ostracism remain open, the current study provided further insight into the impact of attributions on evaluation of ostracism sources and targets.

When Silence Is Not Golden: Why Acknowledgment Matters Even When Being Excluded - Selma C. Rudert; Andrew H. Hales; Rainer Greifeneder; Kipling D. Williams (Personality and Social Psychology Bulletin, 2017)
Following ostracism, individuals are highly sensitive to social cues. Here we investigate whether and when minimal acknowledgment can improve need satisfaction following an ostracism experience. In four studies, participants were either ostracized during Cyberball (Studies 1 and 2) or through a novel apartment-application paradigm (Studies 3 and 4). To signal acknowledgment following ostracism, participants were either thrown a ball a few times at the end of the Cyberball game, or received a message that was either friendly, neutral, or hostile in the apartment-application paradigm. Both forms of acknowledgment increased need satisfaction, even when the acknowledgment was hostile (Study 4), emphasizing the beneficial effect of any kind of acknowledgment following ostracism. Reinclusion buffered threat immediately, whereas acknowledgment without reinclusion primarily aided recovery. Our results suggest that minimal acknowledgment such as a few ball throws or even an unfriendly message can reduce the sting of ostracism.

When It’s Okay That I Don’t Play: Social norms and the situated construal of social exclusion. - Selma C. Rudert; Rainer Greifeneder (Personality and Social Psychology Bulletin, 2016)
Being excluded and ignored has been shown to threaten fundamental human needs and cause pain. Such reflexive reactions to social exclusion have been conceptualized as direct and unmoderated (temporal need threat model of ostracism). Here, we propose an extension and argue that reflexive reactions depend on how social exclusion situations are construed. If being excluded is understood as a violation of an inclusion norm, individuals will react with pain and threat. In contrast, if being excluded is consistent with the prevailing norm, the exclusion situation is interpreted as less threatening, and negative reflexive reactions to ostracism should be attenuated. Four studies empirically support this conceptual model. Studies 3 and 4 further show that to guide situated construal, the norm has to be endorsed by the individual. In both Studies 1 and 3, the effect of the norm is mediated by the objective situation’s subjective construal.

An unscathed past in the face of death: Mortality salience reduces individuals' regrets - Selma Carolin Rudert; Leonie Reutner; Mirella Walker; Rainer Greifeneder (Journal of Experimental Social Psychology, 2015)
Folk wisdom and popular literature hold that, in the face of death, individuals tend to regret things in their lives that they have done or failed to do. Terror Management Theory (TMT), in contrast, allows for the prediction that individuals who are confronted with death try to minimize the experience of regret in order to retain a positive self-esteem. Three experiments put these competing perspectives to test. Drawing on TMT, we hypothesized and found that participants primed with their own death regret fewer things than control-group participants. This pattern of results cannot be attributed to differing types of regrets (Study 1). Furthermore, we provide evidence suggesting that the effect is not purely a product of cognitive mechanisms such as differing levels of construal (Study 2), cognitive contrast, or deficits (Study 3). Rather, the reported results are best explained in terms of a motivational coping mechanism: When death is salient, individuals strive to bolster as well as protect their self-esteem and accordingly try to minimize the experience of regret. The results add to our conceptual understanding of regret and TMT, and suggest that a multitude of lifestyle guidebooks need updating.

“Attitudes Towards Languages” (AToL) Scale: A global instrument - Christiane Schoel; Janin Roessel; Jennifer Eck; Jana Janssen; Branislava Petrovic; Astrid Rothe; Selma Carolin Rudert; Dagmar Stahlberg (Journal of Language and Social Psychology, 2012)
Language attitudes may be differentiated into attitudes towards speakers and attitudes towards languages. However, to date, no systematic and differentiated instrument exists that measures attitudes towards language. Accordingly, we developed, validated, and applied the Attitudes Towards Languages (AToL) scale in four studies. In Study 1, we selected 15 items for the AToL scale, which represented the three dimensions of value, sound, and structure. The following studies replicated and validated the three-factor structure and differential mean profiles along the three dimensions for different languages (a) in a more diverse German sample (Study 2), (b) in different countries (Study 3), and (c) when participants based their evaluations on speech samples (Study 4). Moreover, we investigated the relation between the AToL dimensions and stereotypic speaker evaluations. Results confirm the reliability, validity, and generalizability of the AToL scale and its incremental value to mere speaker evaluations.

Aktuelle Spracheinstellungen in Deutschland - Erste Ergebnisse einer bundesweiten Repräsentativumfrage. - L. Eichinger; A.-K. Gärtig; A. Plewnia; J. Rössel; A. Rothe; Selma Carolin Rudert; C. Schöl; D. Stahlberg (Institut für Deutsche Sprache, 2009)